Outlander. Season six [videorecording (DVD)] - Moore, Ronald D. (Sony Pictures Home Entertainment, 2022)
Establishing a home in the New World is by no means an easy task, particularly in the wild backcountry of North Carolina during a period of dramatic political upheaval. The Frasers strive to flourish within a society which, as Claire knows all too well, is unwittingly marching towards Revolution. Jamie must now defend this home established on land granted to him by the Crown although this new mantle of responsibility sees him pitted against his godfather, Murtagh Fitzgibbons, a leader of the Regulator Rebellion.